PENINGKATAN KETERAMPILAN MENULIS SURAT RESMI DENGAN MENGGUNAKAN STRATEGI MENYUSUN KARTU(CARD SORT) - Neti, Yustina (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2018)
This action research aims to describe the planning, implementation and evaluation of learning preparing a formal letter with the strategy card (card sort) in Class VIII B SMP Negeri 1 Establish Year 2011/2012. The method used is descriptive, qualitative research is the shape and type of research is classroom action research. This study using the technique of direct observation and measurement techniques. The results showed that the strategy set the cards (Card sort) managed to improve the ability of students to write a formal letter. In cycle 1 gained an average of 66.70 with a passing grade of 30%, can be classified is still low, at 2 cycles increased by an average of 70.85 with 55% mastery learning there are students who have not completed the necessary improvements and cycle 3 achieved an average 73.17 and completeness study 85% said learning has managed in accordance with the expected goals.